A strategy to enhance overall efficiency for dye-sensitized solar cells with a transparent electrode of nickel sulfide decorated with poly(3, 4-ethylenedioxythiophene). Issue 54 (13th June 2015) - Ma, Xingping; Yue, Gentian; Wu, Jihuai; Lan, Zhang; Lin, Jeng-Yu
<x xml:space="preserve">Abstract</x> DSSC with NiS/PEDOT CE and aluminum foil as the reflector, Jsc = 18.19 mA cm−2, Voc = 0.751 V, FF = 0.62, PCE = 8.47%.